(untitled) (Sociologisk Forskning, 2018)
Studying the Economic Elite – Problems and Challenges This article presents my experiences of studying Djursholm as Sweden’s ”Leader Community” during 2010 through 2015. I address the relative lack of studies of the economic elite, which is a problem both for the sociological literature, and for public debate. The reason to why relatively few studies have been made of the economic elite, particularly in Sweden, has amongst others to do with a reputation of it as being hard to study, not at least due to this group’s often social closure. By proposing examples from my own study, I try to describe how studies of the economic elites can be done with a view of generating more research of this anonymous yet influential group.